Hansen’s Disease with Pure Nerve Involvement and Perineural Abscess Mistaken for Peripheral Nerve Sheath Tumour - Moinuddin Sultan; Mitali Choudhary; Mazain Siddique; Nihal Lavhale; Padma Vikram Badhe (European Medical Journal)
Department of Radiology, Vedantaa Institute of Medical Sciences, Dahanu, India